2005
DOI: 10.1093/treephys/25.6.681
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mass inoculation on induced oleoresin response in intensively managed loblolly pine

Abstract: Oleoresin flow is an important factor in the resistance of pines to attack by southern pine beetle, Dendroctonus frontalis Zimm., and its associated fungi. Abiotic factors, such as nutrient supply and water relations, have the potential to modify this plant-insect-fungus interaction; however, little is known of the effects of inoculation with beetle-associated fungi on oleoresin flow. We observed that constitutive and induced resin yield in loblolly pine, Pinus taeda L., were affected by either fungal inoculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 47 publications
4
30
1
Order By: Relevance
“…In addition, this fungus is not specific to the bark beetle, as it is found with many bark beetles including species that colonize weakened, dying, or dead trees (47,64,101). This fungus initiates a moderate induced defense response in pines (22,40,51,75).…”
Section: Lessons Learned From the Dendroctonus Frontalis-fungus Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, this fungus is not specific to the bark beetle, as it is found with many bark beetles including species that colonize weakened, dying, or dead trees (47,64,101). This fungus initiates a moderate induced defense response in pines (22,40,51,75).…”
Section: Lessons Learned From the Dendroctonus Frontalis-fungus Systemmentioning
confidence: 99%
“…Notably, observations that O. minus was not always present, or present only in small amounts, in trees killed by D. frontalis brought into question the role of this fungus in tree killing. Furthermore, inoculation studies indicated that O. minus is not capable of killing mature pines (51). Perhaps most revealing were observations that tunneling larvae of D. frontalis turn away from phloem colonized by O. minus and do not survive when they cannot avoid feeding in O. minus-colonized areas (6,63).…”
Section: Lessons Learned From the Dendroctonus Frontalis-fungus Systemmentioning
confidence: 99%
“…These affirmations are confirmed in the present study. Furthermore, the inoculation technique, the amount of inoculum and the physiological state of the tree can have an influence in the tree being easily colonized (Klepzig et al, 2005).…”
Section: Anatomy Of the Inoculated Stem Of Pinus Hartwegiimentioning
confidence: 99%
“…A appears to be more beneficial) and are carried within specialized structures called mycangia, in the beetle. Ophiostoma minus (Hedgcock) H. and P. Sydow is a socalled bluestain fungus which aids the beetle in depleting host defences (Klepzig et al, 2005), but later acts antagonistically, competing with the mycangial fungi and larvae for uncolonized phloem (Barras, 1970;Klepzig and Wilkens, 1997).…”
Section: Introductionmentioning
confidence: 99%